Visualizing sensuous suffering and affective pain in early modern Europe and the Spanish Americas - Graham, Heather, 1978-; Kilroy-Ewbank, Lauren (Brill's studies in intellectual history, 2018)
Visualizing sensuous suffering and affective pain in Early Modern Europe and the Spanish Americas' is a trans-cultural collection of studies on visual treatments of the phenomena of suffering and pain in early modern culture. Ranging geographically from Italy, Spain, and the Low Countries to Chile, Mexico, and the Philippines and chronologically from the fourteenth to the eighteenth centuries, these studies variously consider pain and suffering as somatic, emotional, and psychological experiences. From examination of bodies shown victimized by brutal public torture to the sublimation of physical suffering conveyed through the incised lines of Counter-Reformation engravings, the authors consider depictions of pain and suffering as conduits to the divine or as guides to social behaviour; indeed, often the two functions overlap.